The History and Identity of Professional and Psychological Disclosure of Teachers in Higher Education Context - Mark Treve (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The researcher investigated the history of the identity of teachers and the factors that create their professional and technical skills in a second-language environment in English. It also highlights the key challenges and provides the literature used in this study with a vivid picture. The researcher sampled 20 informants at Thai University, both Native (n=7) and Non-Native English Professors (n=13). The researcher used a research design of mixed methods. The quantitative data and factual scenarios of the informants' teachings were examined. At the same time, the researcher was able to look into the life of participants involved in the study through detailed personal stories. The findings have shown that the primary focal areas of the teachers are achievement of students, the institutional assessment, and other areas, like the choice of approach to teaching, job satisfaction, socio-economic concerns and concerns of native and non-native speakers that influence the identity of teachers in the 21st century, either directly or indirectly. The majority of the informants were concerned about this issue.